2005
DOI: 10.1093/chemse/bji054
|View full text |Cite
|
Sign up to set email alerts
|

Initial Licking Responses of Mice to Sweeteners: Effects of Tas1r3 Polymorphisms

Abstract: Recent studies have established that the T1R3 receptor plays a central role in the taste-mediated ingestive response to sweeteners by mice. First, transgenic mice lacking the gene for T1R3, Tas1r3, show dramatically reduced lick responsiveness to most sweeteners. Second, strains with the taster allele of Tas1r3 (T strains) are more sensitive to low sweetener concentrations than strains with the nontaster allele (NT strains) and consume greater quantities of low- to midrange concentrations of sweeteners during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
46
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 74 publications
8
46
0
1
Order By: Relevance
“…Another factor considered was effectiveness at evoking gustatory responses, so when possible concentrations were chosen that evoke CT responses at least one-half as large as the response to 100 mM NH 4 Cl (Inoue et al, 2001). In addition, all of the sweeteners were used at concentrations equal or close to those which are consumed to a greater extent by B6 than 129 mice in 48 h two-bottle tests with water , although 500 mM sucrose, 1 mM SC-45647, and 750 mM glycine are consumed more avidly by 129 mice in short-term intake tests (Dotson and Spector, 2004;Glendinning et al, 2005). The amino acids were included based on evidence that they taste sweet to mice, but the previous data on them are complex.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor considered was effectiveness at evoking gustatory responses, so when possible concentrations were chosen that evoke CT responses at least one-half as large as the response to 100 mM NH 4 Cl (Inoue et al, 2001). In addition, all of the sweeteners were used at concentrations equal or close to those which are consumed to a greater extent by B6 than 129 mice in 48 h two-bottle tests with water , although 500 mM sucrose, 1 mM SC-45647, and 750 mM glycine are consumed more avidly by 129 mice in short-term intake tests (Dotson and Spector, 2004;Glendinning et al, 2005). The amino acids were included based on evidence that they taste sweet to mice, but the previous data on them are complex.…”
Section: Methodsmentioning
confidence: 99%
“…The former consume larger volumes of diverse sweeteners in 48 h tests ) and have larger whole-nerve chorda tympani (CT) responses to sweeteners (Inoue et al, 2001), as one would expect if these compounds taste sweeter to the B6 strain. However, in short-duration paradigms designed to emphasize the role of gustation, B6 mice have smaller intakes of some concentrations of the sweeteners sucrose and SC-45647 than do 129 mice (Dotson and Spector, 2004;Glendinning et al, 2005). This discrepancy may arise because the large 48 h intakes of B6 mice are driven by postingestive effects.…”
Section: Introductionmentioning
confidence: 99%
“…Saccharide acceptance (total intake) and preference (relative intake) are influenced by both taste and post-oral factors. To minimize post-oral factors, a brief-access (60 s) two-bottle test was used (10). Because intake volumes are very low in such short tests, licking responses to the saccharide and water sipper spouts rather than intakes were recorded.…”
Section: Experiments 1: 60-s Two-bottle Testsmentioning
confidence: 99%
“…Selective elimination of these receptor proteins in knockout mice attenuates or completely blocks the behavioral and gustatory nerve responses to sugars and artificial sweeteners (7,40). Further, allelic variation in the Tas1r3 gene, which codes for the T1R3 protein (3,(17)(18)(19)24), contributes to strain differences in sensitivity (9), lick responsiveness (8,10), peripheral taste nerve responsiveness (11), and daily intake and preference (11,22) for sugars and artificial sweeteners.…”
mentioning
confidence: 99%
“…This strain is characterized by a form of the T1R3 taste receptor that is ineffective at binding sugars (Nie et al 2005), and 129 mice have small taste-evoked responses to sweeteners in the CT and NST compared with B6 mice (Inoue et al 2001;McCaughey 2007). However, there is a discrepancy between these findings and the results of short-term licking tests, in which 129 mice lick mid-to-high concentrations of sweeteners to the same extent as B6 mice (Dotson and Spector 2004;Glendinning et al 2005). Our findings may help to resolve this issue, because we observed that sucrose responses were large in B cells of 129 mice, but small in B cells of B6 mice.…”
Section: Bursting By Nst Cells May Increase Their Impact On Postsynapmentioning
confidence: 99%